Education for the ASEAN Community – The Case of Indonesia - Pingkan Umboh (Centre for Business and Diplomatic Studies (CBDS) Bina Nusantara University, 2013)
Education plays a significant role in all of the strategies made and initiatives taken to achieve various outcomes of ASEAN. One of the core strategies which engage the Higher Education sector to meet the ASEAN Community in 2015 was “Cross‐border mobility and internationalisation of education—to promote regional sharing, cultivate a regional perspective among member states and contribute to the spirit of regional unity and excellence.” The purpose of this practice note is to find and analyse initiatives taken by the Government and Higher Education institutions focussing in Indonesia, the largest population and largest economy country in ASEAN and how the initiatives positioned the education in the region. This note is intended to contribute to the knowledge of ASEAN Community, especially on its education area.